Benchmarking study on continuum-based granular flow dynamics models for simulating the drag finishing process on a CFD framework. (1st January 2014) - Ten, Jyi Sheuan; Wan, Stephen
Drag finishing is a mass finishing technique in which workpieces are dragged through a mass of granular media contained in a stationary drum. Only a small portion of the media immediately surrounding the workpieces actually flows, with a shear band separating this fluid region and the static, solid-like portions that occupy most of the drum. In this presentation, we report on our benchmarking of two promising granular flow dynamics models. The models were input into ANSYS FLUENT as user-defined functions and simulation results were compared against experimental data found in the open literature.